The ethical principles and caring behavior of Indonesian nurses - Ilkafah Ilkafah; Anestasia Pangestu Mei Tyas; Rini Rachmawaty (PAGEPress Publications, 2023)
Introduction: The caring behavior of nurses affects their working performance and the health care quality received by patients. The adherence to ethical principles by nurses is also known to increase this factor. However, no previous studies have been conducted on how ethical principles affect the caring behaviors of nurses. Hence, this study aims to investigate the association between nursing ethics and other demographic characteristics and their caring behavior in Indonesian hospitals. Design and Methods: A cross-sectional descriptive-analytical study was conducted with 389 nurses working in Indonesian hospitals. Furthermore, data were collected using questionnaires, which included demographic characteristics, ethical principles-based attitudes, and caring behavior. The analysis of the data was performed using descriptive (M, SD) and inferential statistics (Chi-square, Spearman's rank correlation, Fisher's exact test, and multiple logistic regression) with α= 0.05. Results: According to this study, the caring behavior of nurses was associated with gender (p=0.030) and nursing ethical principles, such as veracity (p=0.025), non-maleficence (p=0.007), beneficence (p<0.000), and fidelity (p<0.000). Fidelity was also revealed as the most influential ethical principle on nurses' caring behavior, with a value of Exp(B)= 3.446. This indicates that nurses, who had demonstrated good fidelity, cared three times more than those who lacked this quality. Conclusions: Nurses with good ethical principles deliver suitable caring behavior. Hence, applying the right ethics to a patient would result in a great caring attitude, as the principle of ethical behavior is compassion and respectful conduct towards patients.